‘Ship-in-a-Bottle’ Integration of pH-Sensitive 3D Proteinaceous Meshes into Microfluidic Channels - Daniela Serien; Koji Sugioka; Aiko Narazaki (Nanomaterials)
Microfluidic sensors incorporated onto chips allow sensor miniaturization and high-throughput analyses for point-of-care or non-clinical analytical tools. Three-dimensional (3D) printing based on femtosecond laser direct writing (fs-LDW) is useful for creating 3D microstructures with high spatial resolution because the structures are printed in 3D space along a designated laser light path. High-performance biochips can be fabricated using the ‘ship-in-a-bottle’ integration technique, in which functional microcomponents or biomimetic structures are embedded inside closed microchannels using fs-LDW. Solutions containing protein biomacromolecules as a precursor can be used to fabricate microstructures that retain their native protein functions. Here, we demonstrate the ship-in-a-bottle integration of pure 3D proteinaceous microstructures that exhibit pH sensitivity. We fabricated proteinaceous mesh structures with gap sizes of 10 and 5 μm. The sizes of these gaps changed when exposed to physiological buffers ranging from pH of 4 to 10. The size of the gaps in the mesh can be shrunk and expanded repeatedly by changing the pH of the surrounding buffer. Fs-LDW enables the construction of microscopic proteinaceous meshes that exhibit dynamic functions such as pH sensing and might find applications for filtering particles in microfluidic channels.